2019
DOI: 10.24283/hjns.20192.11-12
|View full text |Cite
|
Sign up to set email alerts
|

Nursing personnel’s knowledge regarding pressure sore management in a public hospital’s medical and surgical wards

Abstract: Introduction: Despite the recent advances in ulcer treatment and management, and the immense advancements in technology, pressure ulcers are still a major challenge for nurses and doctors who are responsible for their management. Aim: The aim of the present study was to investigate the knowledge, practices and attitudes of nursing staff in a large public hospital regarding prevention and management of pressure ulcers. Methods: This study is a research cross-sectional study which involved all nursing staff (nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study of Qaddumi and Khawaldeh 17 in Jordan, revealed that nurses had insufficient knowledge regarding the prevention of pressure ulcers. In a similar study, by Dimou et al, 18 with 92 nurses working in medical and surgical departments of a general hospital in Greece, nurses had high levels of knowledge regarding the definition and the staging of pressure ulcers while they had a reasonable level of knowledge about pressure ulcers in total.…”
Section: Discussionmentioning
confidence: 77%
“…A study of Qaddumi and Khawaldeh 17 in Jordan, revealed that nurses had insufficient knowledge regarding the prevention of pressure ulcers. In a similar study, by Dimou et al, 18 with 92 nurses working in medical and surgical departments of a general hospital in Greece, nurses had high levels of knowledge regarding the definition and the staging of pressure ulcers while they had a reasonable level of knowledge about pressure ulcers in total.…”
Section: Discussionmentioning
confidence: 77%